Land‐Use Effects on Surface Water Quality in Temperate Lowland Peatlands - Teresa Silverthorn; Dan Aberg; Francesca Baker; Chris Bell; Chris D. Evans; Caroline Gurd; Ian Holman; Graham Howell; Angus McEwen; Ross Morrison; Josh Oakley; Francesca Southon; et al. (Global Change Biology, 2026)
Peatlands are important ecosystems for carbon storage, water regulation, water quality and other valuable ecosystem services that have been heavily impacted by drainage and conversion to grassland and cropland. Rewetting, or raising of the water table closer to the ground surface, is proposed as a solution to reduce peatland subsidence and carbon losses. Both peatland drainage and peatland rewetting may have unintended impacts on water quality, either by introducing solutes from the water used for rewetting, or by leaching of substances accumulated in peat. Here, we examined the effects of land use on UK lowland peat surface water chemistry by collecting a total of 350 surface water samples from 77 individual water bodies (ditches, streams, ponds) in 2024, across 33 sites representing the range of temperate lowland peatland types. Samples were measured for a wide array of chemical determinands including: carbon (C), nitrogen (N) and phosphorus (P), heavy metals, other anions and cations, and dissolved greenhouse gas concentrations. We found some clear patterns related to land use, notably high nitrate concentrations in surface waters draining croplands. Macronutrient stoichiometry revealed similar patterns at grassland, conservation‐managed and rewetted sites indicative of N and P co‐limitation, suggesting that rewetting leads to a nutrient balance comparable to natural conditions. Peatland type (bog vs. fen) was more important than land use in explaining patterns in most ion concentrations. Site and regional histories were more important than land use for patterns of heavy metal concentrations, indicating the importance of considering regional historical industrial activity. Overall, peatland land use can be an important driver of key nutrients and their stoichiometry, with no consistent negative impacts of peatland rewetting on water quality nor greenhouse gases.

A generalized linear mixed model approach to assess associations between Certified Food Protection Managers and inspection performance in Franklin County, Ohio - Allison Howell; Alexander Evans; Sarah Jensen; Nicole L. Arnold; Barbara Kowalcyk (Food Control, 2026)

Re-assessment of a large archosaur dentary from the Late Triassic of South Wales, United Kingdom - Owain Evans; Cindy Howells; Nathan Wintle; Michael J. Benton (Proceedings of the Geologists' Association, 2025)

Wheat genetic resources have avoided disease pandemics, improved food security, and reduced environmental footprints: A review of historical impacts and future opportunities - Julie King; Susanne Dreisigacker; Matthew Reynolds; Anindya Bandyopadhyay; Hans‐Joachim Braun; Leonardo Crespo‐Herrera; Jose Crossa; Velu Govindan; Julio Huerta; Maria Itria Ibba; Carlos A. Robles‐Zazueta; Carolina Saint Pierre; et al. (Global Change Biology, 2024)
The use of plant genetic resources (PGR)—wild relatives, landraces, and isolated breeding gene pools—has had substantial impacts on wheat breeding for resistance to biotic and abiotic stresses, while increasing nutritional value, end‐use quality, and grain yield. In the Global South, post‐Green Revolution genetic yield gains are generally achieved with minimal additional inputs. As a result, production has increased, and millions of hectares of natural ecosystems have been spared. Without PGR‐derived disease resistance, fungicide use would have easily doubled, massively increasing selection pressure for fungicide resistance. It is estimated that in wheat, a billion liters of fungicide application have been avoided just since 2000. This review presents examples of successful use of PGR including the relentless battle against wheat rust epidemics/pandemics, defending against diseases that jump species barriers like blast, biofortification giving nutrient‐dense varieties and the use of novel genetic variation for improving polygenic traits like climate resilience. Crop breeding genepools urgently need to be diversified to increase yields across a range of environments (>200 Mha globally), under less predictable weather and biotic stress pressure, while increasing input use efficiency. Given that the ~0.8 m PGR in wheat collections worldwide are relatively untapped and massive impacts of the tiny fraction studied, larger scale screenings and introgression promise solutions to emerging challenges, facilitated by advanced phenomic and genomic tools. The first translocations in wheat to modify rhizosphere microbiome interaction (reducing biological nitrification, reducing greenhouse gases, and increasing nitrogen use efficiency) is a landmark proof of concept. Phenomics and next‐generation sequencing have already elucidated exotic haplotypes associated with biotic and complex abiotic traits now mainstreamed in breeding. Big data from decades of global yield trials can elucidate the benefits of PGR across environments. This kind of impact cannot be achieved without widescale sharing of germplasm and other breeding technologies through networks and public–private partnerships in a pre‐competitive space.

Creating Pathways for Nontraditional Graduate Students - Phoebe Woodworth-Jefcoats; Mackenzie Jahnke; Evan Howell; Donald Kobayashi; Chad Miller; Ryan Nichols; Megan Onuma (Oceanography, 2023)
As past and present nontraditional students, our group of authors experienced firsthand a range of hurdles in our pursuit of ocean science graduate studies. Some of us attended graduate school while working full time in our fields as a means to advance our careers. Others returned to graduate school to pursue a second career in a new field. Combining our experiences with broader demographic information (Wendler et al., 2010) led us to define nontraditional ocean science graduate students as any of the following: mid-career professionals pursuing graduate degrees for career advancement and those who are embarking on a second career, hold an undergraduate degree outside of STEM, are in their thirties or older, or are balancing school with work and/or family responsibilities. While we highlight these characteristics, we recognize that there are others who self-identify as nontraditional, such as those facing a serious medical condition or disability. We hope that by sharing ways to remove barriers to entry, retention, and advancement for nontraditional students, our field will become more inclusive, equitable, and diverse.

Extended gene panel testing in lobular breast cancer - Elke M. van Veen; D. Gareth Evans; Elaine F. Harkness; Helen J. Byers; Jamie M. Ellingford; Emma R. Woodward; Naomi L. Bowers; Andrew J. Wallace; Sacha J. Howell; Anthony Howell; Fiona Lalloo; William G. Newman; et al. (Familial Cancer, 2022)
Purpose : Lobular breast cancer (LBC) accounts for ~ 15% of breast cancer. Here, we studied the frequency of pathogenic germline variants (PGVs) in an extended panel of genes in women affected with LBC. Methods : 302 women with LBC and 1567 without breast cancer were tested for BRCA1/2 PGVs. A subset of 134 LBC affected women who tested negative for BRCA1/2 PGVs underwent extended screening, including: ATM, CDH1, CHEK2, NBN, PALB2, PTEN, RAD50, RAD51D, and TP53. Results : 35 PGVs were identified in the group with LBC, of which 22 were in BRCA1/2 . Ten actionable PGVs were identified in additional genes ( ATM (4), CDH1 (1), CHEK2 (1), PALB2 (2) and TP53 (2)). Overall, PGVs in three genes conferred a significant increased risk for LBC. Odds ratios (ORs) were: BRCA1 : OR = 13.17 (95%CI 2.83–66.38; P = 0.0017), BRCA2 : OR = 10.33 (95%CI 4.58–23.95; P < 0.0001); and ATM: OR = 8.01 (95%CI 2.52–29.92; P = 0.0053). We did not detect an increased risk of LBC for PALB2, CDH1 or CHEK2 . Conclusion : The overall PGV detection rate was 11.59%, with similar rates of BRCA1/2 (7.28%) PGVs as for other actionable PGVs (7.46%), indicating a benefit for extended panel genetic testing in LBC. We also report a previously unrecognised association of pathogenic variants in ATM with LBC.

Accommodating the role of site memory in dynamic species distribution models - Graziella V. DiRenzo; David A. W. Miller; Blake R. Hossack; Brent H. Sigafus; Paige E. Howell; Erin Muths; Evan H. C. Grant (Ecology, 2021)
First‐order dynamic occupancy models (FODOMs) are a class of state‐space model in which the true state (occurrence) is observed imperfectly. An important assumption of FODOMs is that site dynamics only depend on the current state and that variations in dynamic processes are adequately captured with covariates or random effects. However, it is often difficult to understand and/or measure the covariates that generate ecological data, which are typically spatiotemporally correlated. Consequently, the non‐independent error structure of correlated data causes underestimation of parameter uncertainty and poor ecological inference. Here, we extend the FODOM framework with a second‐order Markov process to accommodate site memory when covariates are not available. Our modeling framework can be used to make reliable inference about site occupancy, colonization, extinction, turnover, and detection probabilities. We present a series of simulations to illustrate the data requirements and model performance. We then applied our modeling framework to 13 yr of data from an amphibian community in southern Arizona, USA. In this analysis, we found residual temporal autocorrelation of population processes for most species, even after accounting for long‐term drought dynamics. Our approach represents a valuable advance in obtaining inference on population dynamics, especially as they relate to metapopulations.

Should unaffected female BRCA2 pathogenic variant carriers be told there is little or no advantage from risk reducing mastectomy? - D. Gareth Evans; Sacha J. Howell; Anthony Howell (Familial Cancer, 2019)

Risk algorithms that include pathology adjustment for HER2 amplification need to make further downward adjustments in likelihood scores - D. G. Evans; E. R. Woodward; S. J. Howell; S. Verhoef; A. Howell; F. Lalloo (Familial Cancer, 2017)

Risk of contralateral breast cancer in BRCA1 and BRCA2 mutation carriers: a 30-year semi-prospective analysis - N. N. Basu; S. Ingham; J. Hodson; F. Lalloo; M. Bulman; A. Howell; D. G. Evans (Familial Cancer, 2015)

Enhancing the TurtleWatch product for leatherback sea turtles, a dynamic habitat model for ecosystem‐based management - Evan A. Howell; Aimee Hoover; Scott R. Benson; Helen Bailey; Jeffrey J. Polovina; Jeffrey A. Seminoff; Peter H. Dutton (Fisheries Oceanography, 2015)
Fishery management measures to reduce interactions between fisheries and endangered or threatened species have typically relied on static time‐area closures. While these efforts have reduced interactions, they can be costly and inefficient for managing highly migratory species such as sea turtles. The NOAA TurtleWatch product was created in 2006 as a tool to reduce the rates of interactions of loggerhead sea turtles with shallow‐set longline gear deployed by the Hawaii‐based pelagic longline fishery targeting swordfish. TurtleWatch provides information on loggerhead habitat and can be used by managers and industry to make dynamic management decisions to potentially reduce incidentally capturing turtles during fishing operations. TurtleWatch is expanded here to include information on endangered leatherback turtles to help reduce incidental capture rates in the central North Pacific. Fishery‐dependent data were combined with fishing effort, bycatch and satellite tracking data of leatherbacks to characterize sea surface temperature ( SST ) relationships that identify habitat or interaction ‘hotspots’. Analysis of SST identified two zones, centered at 17.2° and 22.9°C, occupied by leatherbacks on fishing grounds of the Hawaii‐based swordfish fishery. This new information was used to expand the TurtleWatch product to provide managers and industry near real‐time habitat information for both loggerheads and leatherbacks. The updated TurtleWatch product provides a tool for dynamic management of the Hawaii‐based shallow‐set fishery to aid in the bycatch reduction of both species. Updating the management strategy to dynamically adapt to shifts in multi‐species habitat use through time is a step towards an ecosystem‐based approach to fisheries management in pelagic ecosystems.

The Fate of Fisheries Oceanography: Introduction to the Special Issue - Steven Bograd; Elliott Hazen; Evan Howell; Anne Hallowed (Oceanography, 2014)

Breast cancer risk assessment in 8,824 women attending a family history evaluation and screening programme - D. Gareth R. Evans; Sarah Ingham; Sarah Dawe; L. Roberts; F. Lalloo; A. R. Brentnall; P. Stavrinos; Anthony Howell (Familial Cancer, 2014)

Mammographic surveillance in women aged 35–39 at enhanced familial risk of breast cancer (FH02) - D. G. Evans; S. Thomas; J. Caunt; L. Roberts; A. Howell; M. Wilson; R. Fox; D. M. Sibbering; S. Moss; M. G. Wallis; D. M. Eccles; S. Duffy (Familial Cancer, 2014)

Climate-induced primary productivity change and fishing impacts on the Central North Pacific ecosystem and Hawaii-based pelagic longline fishery - Evan A. Howell; Colette C. C. Wabnitz; John P. Dunne; Jeffrey J. Polovina (Climatic Change, 2013)

Estimating the carrying capacity of French Frigate Shoals for the endangered Hawaiian monk seal using Ecopath with Ecosim - Frank A. Parrish; Evan A. Howell; George A. Antonelis; Sara J. Iverson; Charles L. Littnan; James D. Parrish; Jeffrey J. Polovina (Marine Mammal Science, 2012)
The carrying capacity of the French Frigate Shoals (FFS) region for the endangered Hawaiian monk seal was appraised using an updated version of the original FFS Ecopath model ( Polovina 1984 ). Model parameters were updated using recent literature, and data from surveys of the seal population and its bottom‐associated prey. Together they produced a static mass balance model for 1998 when the prey surveys began. The Ecopath‐estimated monk seal biomass was 0.0045 t/km 2 , which was in close agreement with the biomass calculated from monk seal field beach counts (0.0046 t/km 2 ). Model simulations through time were done in Ecosim using the Ecopath balanced model and included fisheries data time series from 1998 to 2008. Monk seal biomass declined concurrently with decreases in benthic bottomfish biomass, which were influenced by large‐scale changes in the environment of the North Pacific. This model scenario was extended from 2010, when the last permitted fishery in the Northwestern Hawaiian Islands was closed, through to 2040, assuming a constant environmental signal. Model results for this time period did not show a recovery of monk seals that exceeded the initial 1998 model biomass levels, highlighting the importance of including environmental variability in estimates of monk seals recovery at FFS.

Breast cancer susceptibility variants alter risk in familial ovarian cancer - A. Latif; H. J. McBurney; S. A. Roberts; F. Lalloo; A. Howell; D. G. Evans; W. G. Newman (Familial Cancer, 2010)

RASSF1A polymorphism in familial breast cancer - J. Bergqvist; A. Latif; S. A. Roberts; K. D. Hadfield; F. Lalloo; A. Howell; D. G. Evans; W. G. Newman (Familial Cancer, 2010)

Oceanographic influences on the dive behavior of juvenile loggerhead turtles (Caretta caretta) in the North Pacific Ocean - Evan A. Howell; Peter H. Dutton; Jeffrey J. Polovina; Helen Bailey; Denise M. Parker; George H. Balazs (Marine Biology, 2010)

Multiple dextranases from the yeast Lipomyces starkeyi - Stefan H. Millson; Ivor Howell Evans (Antonie van Leeuwenhoek, 2007)

Adult weight gain and central obesity in women with and without a family history of breast cancer: a case control study - Michelle N. Harvie; Saba Bokhari; Andrew Shenton; Linda Ashcroft; Gareth Evans; Ric Swindell; Anthony Howell (Familial Cancer, 2007)

El Niño effects in the Palmyra Atoll region: oceanographic changes and bigeye tuna ( Thunnus obesus ) catch rate variability - EVAN A. HOWELL; DONALD R. KOBAYASHI (Fisheries Oceanography, 2006)
A generalized additive model (GAM) was constructed to separate and quantify the effects of fishery‐based (operational) and oceanographic parameters on the bigeye tuna ( Thunnus obesus ) catch rates at Palmyra Atoll in the central Tropical Pacific. Bigeye catch, the number of hooks per set, and set location from 4884 longline sets spanning January 1994 to December 2003 were used with a temporally corresponding El Niño‐Southern Oscillation (ENSO) indicator built from sea surface height (SSH) data. Observations of environmental data combined with the results from the GAM indicated that there is an increase in bigeye catch rates corresponding to an increase in eastward advection during the winter months of El Niño events. A seasonal pattern with higher bigeye catch rates from December to April and a spatial pattern with higher rates to the northeast and northwest of the atoll were observed during this study period. It is hypothesized that the combination of the eastward advection of the warm pool coupled with vertical changes in temperature during the winter months of El Niño events increases the availability of bigeye tuna in this region. This increase in availability may be due to a change in exploitable population size, location, or both.

Forage and migration habitat of loggerhead ( Caretta caretta ) and olive ridley ( Lepidochelys olivacea ) sea turtles in the central North Pacific Ocean - Jeffrey J. Polovina; George H. Balazs; Evan A. Howell; Denise M. Parker; Michael P. Seki; Peter H. Dutton (Fisheries Oceanography, 2004)
Satellite telemetry from 26 loggerhead ( Caretta caretta ) and 10 olive ridley ( Lepidochelys olivacea ) sea turtles captured and released from pelagic longline fishing gear provided information on the turtles’ position and movement in the central North Pacific. These data together with environmental data from satellite remote sensing are used to describe the oceanic habitat used by these turtles. The results indicate that loggerheads travel westward, move seasonally north and south primarily through the region 28–40°N, and occupy sea surface temperatures (SST) of 15–25°C. Their dive depth distribution indicated that they spend 40% of their time at the surface and 90% of their time at depths

Control of drosopterin synthesis in Drosophila melanogaster: Mutants showing an altered pattern of GTP cyclohydrolase activity during development - B. A. Evans; A. J. Howells (Biochemical Genetics, 1978)